Designing Game For Spirituality Education At Primary School - Rico Yupita; Ridwan Sanjaya; Bernadinus Harnadi (Soegijapranata Catholic University, 2021)
The purpose of this research is to find out the ways to make Catholic Subject learning more enjoyable, convenient, and helpful by designing